Understanding the instructional leadership practices of exemplar secondary school principals in Kerala, India: A multiple case study - Thomas, Bijumon (Animo Repository, 2020)
The new National Education Policy of India, formulated by the Human Resource Ministry, emphasizes the need to implement and strengthen the instructional leadership behavior of the school principals in order to increase the student learning. However, various studies about schools in India reveal that there is a lack of scientific studies about the practice of instructional leadership by principals. The purpose of the study, therefore, was to uncover the understanding of instructional leadership among exemplar principals and how the principals exercise instructional leadership in the schools to create a framework of instructional leadership. The present study was a qualitative multiple case study of instructional leadership practices of exemplar secondary school principals in Kerala. In-depth interviews with eight exemplar principals were used as the major research tool. The theoretical support is drawn mainly from the works of Hallinger and Murphy on instructional leadership. Specifically, the findings describe where and how exemplar principals spend their time, standards that inform their behavior, and competencies they need to master in order to be effective. The research findings will help the struggling principals to bring about a change in the student achievement and will help policy makers and principal trainers to bring about necessary improvement in their policies and programs. Keywords: instructional leadership, leading the learning, mentoring teachers, student motivation, relationship